Meander Conductor Shape Influence on the Electrodynamic Parameters of the Meander Structures - Belova-Plonienė Diana; Katkevičius Andrius (Electrical, Control and Communication Engineering)
Meander structures allow reducing the size of the microwave devices while keeping the same operational characteristics. The shape of meander makes a considerable impact on the operation of microwave devices. Therefore, the structure of meander is widely investigated nowadays. The review of different shapes of a meander conductor is presented in this article. Two models with different shape of connecting conductors are designed and discussed in detail. The influence of variation of the length and width of connecting conductors on the electrical parameters of the meander is revealed using the traditional model of meander. Later, the comparison of the traditional model and the model with rectangle-shape peripheral parts of a meander conductor is presented. The increase in the width of connecting conductors from 0.2 mm to 1.0 mm has narrowed the bandwidth by 346 MHz until 2.388 GHz. The increase in the length of connecting conductors to 2.3 mm has allowed moving the stop-band to higher frequencies. The usage of the rectangle-shape connecting conductors slightly reduces the pass-band but allows achieving more stable input impedance.